I-125 seed calibration using the SeedSelectron(®) afterloader: a practical solution to fulfill AAPM-ESTRO recommendations - Perez-Calatayud, Jose (Termedia Publishing House, 2012)
PURPOSE: SeedSelectron(®) v1.26b (Nucletron BV, The Netherlands) is an afterloader system used in prostate interstitial permanent brachytherapy with I-125 selectSeed seeds. It contains a diode array to assay all implanted seeds. Only one or two seeds can be extracted during the surgical procedure and assayed using a well chamber to check the manufacturer air-kerma strength (S(K)) and to calibrate the diode array. Therefore, it is not feasible to assay 5–10% seeds as required by the AAPM-ESTRO. In this study, we present a practical solution of the SeedSelectron(®) users to fulfill the AAPM- ESTRO recommendations. MATERIAL AND METHODS: The method is based on: a) the SourceCheck(®) well ionization chamber (PTW, Germany) provided with a PTW insert; b) n = 10 selectSeed from the same batch and class as the seeds for the implant; c) the Nucletron insert to accommodate the n = 10 seeds on the SourceCheck(®) and to measure their averaged S(K). Results for 56 implants have been studied comparing the S(K) value from the manufacturer with the one obtained with the n = 10 seeds using the Nucletron insert prior to the implant and with the S(K) of just one seed measured with the PTW insert during the implant. RESULTS: We are faced with S(K) deviation for individual seeds up to 7.8%. However, in the majority of cases S(K) is in agreement with the manufacturer value. With the method proposed using the Nucletron insert, the large deviations of S(K) are reduced and for 56 implants studied no deviation outside the range of the class were found. CONCLUSIONS: The new Nucletron insert and the proposed procedure allow to evaluate the S(K) of the n = 10 seeds prior to the implant, fulfilling the AAPM-ESTRO recommendations. It has been adopted by Nucletron to be extended to seedSelectron(®) users under request.